Decoding Five Times Extended Reed Solomon Codes Using Syndromes - Farkaš, Peter; Rakús, Martin (Computing and Informatics, 2021)
Recently a new family of five times extended Reed Solomon codes constructed over certain finite fields GF(2 zeta), where zeta >= 3 is an odd integer, was discovered. Until now only an erasure decoding algorithm for these codes was published. In this paper a new decoding algorithm is presented, which allows correcting up to two errors in a codeword from the five times extended Reed Solomon codes. The proposed decoding algorithm is based on syndrome usage.